Determinants of Stock Prices: Case Study of Liquidity and Profitability in the Pulp and Paper Sector on the Indonesia Stock Exchange - Radityo Nugroho (Journal Of Economic Cluster, 2025)
This study aims to analyze the effect of liquidity and profitability on stock prices in the pulp and paper sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The research population includes all listed companies in the sub-sector, with a purposive sampling technique yielding 24 observations from 8 companies. Secondary data were obtained from annual financial reports published on the official IDX website. The analysis method used is multiple linear regression. The results partially show that liquidity has no significant effect on stock prices (t-count -1.573 < t-table 2.064; sig. 0.131). In contrast, profitability has a positive and significant effect on stock prices (t-count 3.825 > t-table 2.064; sig. 0.001). Simultaneously, liquidity and profitability significantly affect stock prices (F-count 9.172 > F-table 3.01; sig. 0.001) with a coefficient of determination (R2) of 46.6%. These findings indicate that investors tend to prioritize earning power as a primary investment signal. For corporate management, these results emphasize the importance of operational efficiency to strengthen profitability and enhance market attractiveness, while exchange authorities could encourage more transparent earnings reporting to maintain stock price stability within this sector